Queue length-based opportunistic relay selection for cooperative wireless networks - Do , Duy Tan; Le , Minh; Nguyen , Van Phuc; Le , Minh Thanh; Dang , Phuoc Hai Trang (Journal of Technical Education Science, 2020)
Cooperative communications have been considered as a powerful technique for enhancing network reliability by increasing the successful packet transmission probability. In this paper, we propose an opportunistic cooperative scheme for single-hop wireless networks that exploits the signal-to-noise ratio and the remaining queue length at each potential relay to choose the best relay for the source-destination link. The best relay (or the winner node) is the relay node that expires their timer first and becomes the helper for the direct link. The proposed method is based on the local channel measurement and requires no topology information. The collision probability of the proposed relay selection scheme is analyzed with the combination between continuous and discrete-time random variables. Simulation results are conducted to evaluate the ability of the proposed scheme in improving the network performance in terms of the packet delivery ratio. The proposed cooperative scheme leads to single-hop wireless network applications such as cellular networks and 802.11-based networks.